2015
DOI: 10.7554/elife.08440
|View full text |Cite
|
Sign up to set email alerts
|

Network structure of brain atrophy in de novo Parkinson's disease

Abstract: We mapped the distribution of atrophy in Parkinson's disease (PD) using magnetic resonance imaging (MRI) and clinical data from 232 PD patients and 117 controls from the Parkinson's Progression Markers Initiative. Deformation-based morphometry and independent component analysis identified PD-specific atrophy in the midbrain, basal ganglia, basal forebrain, medial temporal lobe, and discrete cortical regions. The degree of atrophy reflected clinical measures of disease severity. The spatial pattern of atrophy d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

43
265
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 207 publications
(309 citation statements)
references
References 74 publications
43
265
1
Order By: Relevance
“…Multiple neurodegenerative diseases, including Alzheimer's and Parkinson's diseases, are increasingly conceptualized as arising from trans-neuronal spread of pathogenic misfolded proteins [36,74]. As a result, patterns of neurodegeneration resemble the underlying structural and functional architecture, and are often centered on one or more specific epicenters [60,77,80].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple neurodegenerative diseases, including Alzheimer's and Parkinson's diseases, are increasingly conceptualized as arising from trans-neuronal spread of pathogenic misfolded proteins [36,74]. As a result, patterns of neurodegeneration resemble the underlying structural and functional architecture, and are often centered on one or more specific epicenters [60,77,80].…”
Section: Introductionmentioning
confidence: 99%
“…Later, as pathology involves the neocortices including higher association areas, individuals with PD and "normal" cognition (PD-N) may cross a barrier of barely detectable cognitive problems and develop neuropsychologically classifiable mild cognitive impairment (PD-MCI) and eventually the full picture of dementia (PDD) (Braak et al, 2003;Braak & Del Tredici, 2017). A large body of in vivo evidence supports the staging system (Zarei et al, 2013;Zeighami et al, 2015), although it is not without controversy (Surmeier, Obeso, & Halliday, 2017;Walsh & Selkoe, 2016). By definition, longitudinal studies from postmortem material are not possible, hence, tracing the temporal dynamics of pathology patterns in vivo together with clinical features becomes increasingly important (Fereshtehnejad, Zeighami, Dagher, & Postuma, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…By definition, longitudinal studies from postmortem material are not possible, hence, tracing the temporal dynamics of pathology patterns in vivo together with clinical features becomes increasingly important (Fereshtehnejad, Zeighami, Dagher, & Postuma, 2017). The regional pattern of cortical brain atrophy in PD remarkably resembles the spatial distribution of cognition-related "resting-state" fMRI networks (Zeighami et al, 2015), and the atrophy distribution appears to be predicted by hyperconnective pathways (Yau et al, 2018). Following longitudinal studies in PD patients that demonstrated a regionspecific accelerated cortical thinning (Mak et al, 2015), we were encouraged to test the hypothesis whether the rate of volumetric changes and cortical thinning over time allows for the definition of a cognitive status-dependent pattern in advanced PD.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a recent structural connectivity study based on voxel deformation reported a basal ganglia structural network deficiency in PD in which the degree of GM loss was linked to motor severity [Chou et al, ]. More recently, large structural covariance network [Zeighami et al, ] and functional connectivity analyses [O'Callaghan et al, ] were successfully applied to characterise striatal and cerebellar network change in PD. No studies of PD related limbic structural connectivity alterations are available, despite the early pathophysiological involvement of the limbic system and the putative link with non‐motor symptoms.…”
Section: Introductionmentioning
confidence: 99%